Anticoagulant drugs for patients with atrial fibrillation on dialysis: a systematic analysis and network meta-analysis - Shen, Xian-Feng; Zhang, Chao; Hu, Jun; Zhang, Tao; Ma, Bin (Frontiers in Pharmacology, 2023)
Objective: A lack of clarity persists regarding the efficacy and risks associated with direct oral anticoagulants (DOACs) in end-stage renal disease (ESRD) patients with atrial fibrillation (AF) undergoing dialysis, primarily due to limited retrospective studies. Therefore, the objective of this study was to evaluate the existing data and propose a practical protocol for the clinical utilization of DOACs in ESRD patients with AF undergoing dialysis. Methods: PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials were searched for clinical studies evaluating DOACs in ESRD patients with AF on dialysis published up to 2 February 2023. DOACs included warfarin, dabigatran, apixaban, edoxaban, and rivaroxaban. The outcomes were mortality, ischemic stroke, hemorrhagic stroke, any stroke, gastrointestinal bleeding, major bleeding, intracranial bleeding, and minor bleeding. Results: Compared with placebo, apixaban (HR = 0.97, 95% CI: 0.88–1.07), rivaroxaban (HR = 0.91, 95% CI: 0.76–1.10), and warfarin (HR = 0.96, 95% CI: 0.90–1.01) did not reduce mortality. Regarding direct comparisons of mortality, the comparisons of warfarin vs. apixaban (HR = 0.99, 95% CI: 0.92–1.06), placebo vs. warfarin (HR = 1.04, 95% CI: 0.99–1.11), and rivaroxaban vs. warfarin (HR = 0.96, 95% CI: 0.80–1.14) did not significantly reduce mortality. Based on the surface under the cumulative ranking curve, rivaroxaban (75.53%), warfarin (62.14%), and apixaban (45.6%) were the most effective interventions for managing mortality, and placebo (16.74%) was the worst. Conclusion: In conclusion, rivaroxaban demonstrated efficacy in reducing mortality and the incidence of ischemic stroke, gastrointestinal bleeding, and intracranial hemorrhage. Dabigatran is recommended for the prevention of hemorrhagic stroke. However, caution should be exercised due to the risk of major bleeding. Warfarin can effectively reduce minor bleeding but does not offer significant protection against gastrointestinal or intracranial bleeding. Apixaban was not recommended for mortality reduction or for preventing ischemic or hemorrhagic strokes. Further research will be necessary to establish specific clinical protocols.